Medición de las propiedades reológicas de la galleta tipo soda cracker en la fase de laminado (2016)
In the food industry, due to the large number of components present in an edible product, problems are shown to understand the interaction of raw materials and operating conditions. In the case of crackers Cracker Soda has little knowledge of the behavior of the dough in different phases especially in the stage of rolling, so in this project the effect of the number of layers, thickness of layer and final thickness of the biscuit on the rheological properties of the dough, specifically the elastic and viscous moduli (Storage) (Loss), and the weight of molded cookie before being baked. Similarly, tests were performed in terms of times fermented (foamed and rest) to determine the effects on time in the fermented dough properties during lamination. Some of the results include the fact that considerable changes of modules are not present during rolling, obtaining values that are between 2 and 30% change...